GASTRIC CANCER WITH SOLITARY METASTASIS IN THE TESTIS: A RARE CLINICAL CASE - D. N. Kostromitsky; E. S. Drozdov; S. G. Afanasyev; A. Y. Dobrodeev; A. S. Podyablonsky; L. N. Bondar; A. S. Tarasova (Сибирский онкологический журнал, 2020)
intraduction. Gastric cancer is the most prevalent malignancy in the world. the common metastatic sites of gastric cancer include liver, lymph nodes and peritoneum. testicular metastasis from gastric cancer occurs extremely rare. there are only 15 reports in literature describing cases with testicular metastasis from gastric cancer. Case report. We first report a clinical case of a man presented with metastasis in the left testis and locally advanced gastric cancer. the patient underwent gastrectomy with resection of the transverse colon and left-sided orchofuniculectomy. Postoperative morphological and immunohistological examinations revealed  gastric cancer with metastasis into the testis. He had received 6 cycles of chemotherapy, with no evidence of recurrence within a 9-month follow-up period.